Discovering computers your interactive guide to the digital world - Shelly, Gary B. (Shelly Cashman series, 2012)
Students are guided through the latest trends in computer concepts and technology in an exciting and easy-to-follow format. Updated for currency, DISCOVERING COMPUTERS: COMPLETE provides the most up-to-date information on the latest technology in today's digital world